The Effect of the Color of a Long Cane Used by Individuals who Are Visually Impaired on the Yielding Behavior of Drivers. (September 2017) - Bourquin, Eugene A.; Emerson, Robert Wall; Sauerburger, Dona; Barlow, Janet
Introduction: A new market trend offers long canes for individuals with visual impairments in a variety of colors; however, the impact of these colors is unknown to orientation and mobility (O&M) specialists and individuals who are blind or who have low vision. The authors examined the impact of cane color on drivers' yielding behaviors; also, cane display effectiveness was assessed. Methods: At traffic signal–controlled intersections, drivers' yielding responses (yield–no yield and seconds to crosswalk) were recorded by two raters when a pedestrian presented one of two conditions (display and flagging) with four differently colored long canes (white, black, yellow, and green). Results: In trials where the pedestrian used a flagging cane technique, the white cane achieved 290% more yielding than the green cane, 100% more yielding than the yellow cane, and 40% more yielding than the black. Statistical differences were found between the white-with-red cane and the yellow and green canes. The measure of drivers' latency for moving forward was not statistically different between trials in which a pedestrian displayed a white cane at the crosswalk and trials in which no pedestrians were present. Discussion: Cane color appears to have a substantial effect on drivers' yielding responses. The results also indicate only a slight driver response to a highly visible cane display, confirming the results of previous studies that recommended more potent pedestrian movements to mitigate the threat from turning vehicles. Implications for practitioners: O&M specialists and cane travelers need to consider the options for cane color when using a cane to cross streets. A white cane, flagged at the onset of the walk signal, can achieve more desirable responses from drivers than can the long canes of other colors. More effective cane behaviors exhibited by pedestrians who are visually impaired should always be considered by O&M instructors in order to influence drivers.